System thinking approaches for circular economy: enabling inclusive, synergistic, and eco-effective pathways for sustainable development - Hassan, Hamza; Faggian, Robert (Frontiers in Sustainability, 2023)
The Circular Economy (CE) concept is rapidly gaining space in mainstream policy in many developed countries, but it remains a contested and underdeveloped notion in scientific circles, largely due to its fragmented nature and absence of a unified framework. This fragmentation is attributed to the concept's diverse roots, its varying utilization by distinct interest groups, and its evolution over time.Though there are strong implicit links between CE and sustainability, the explicit connections are seldom addressed. Current CE views tend to heavily concentrate on the economic aspect of sustainability, marginally on the environmental one, and largely neglect the social aspect. The prevailing reductive interpretations of CE often lead to subpar or even unsustainable results, thereby posing significant challenges to its implementation and questioning its legitimacy as a sustainable development model. This systematic literature review, through an examination of CE's varied origins, its role in integrated socio-economic dialogues, its sustainability implications, and the challenges presented by its existing reductive approaches, underscores the necessity for a systemic exploration of the CE concept. Given that CE is rooted in Systems Ecology, adopting a pluralistic, transdisciplinary perspective is crucial to overcome challenges and limitation associated with CE implementation. The authors propose that the implementation of CE must be guided by holistic systemic evaluations of organizations with equal emphasis on environmental and social apprehensions along with economic concerns. Such systemic evaluations can ensure that CE meets its sustainability objectives and remain a legitimate pathway towards sustainable development.